Peningkatan Produktivitas Hasil Pertanian Melalui Pelatihan Pembuatan Pupuk Organik Cair dari Tanaman Purun - Kalalinggi, Septaria Yolan; Kumalasari, Meiyanti Ratna; Beladona, Siti Unvaresi Misonia; Putra, Riandy; Pratika, Remi Ayu (Journal of Appropriate Technology for Community Services, 2025)
The influence of the utilization of chemical fertilizers on agricultural land has a negative impact on the environment since it can reduce soil fertility and pollute air and water. Currently, the use of chemical fertilizers is starting to be reduced. The development of organic fertilizers derived from natural ingredients began to be developed, where the advantages of using organic fertilizers are easy to obtain, environmentally friendly, and low production costs. The Community Empowerment Assistance Lecturer Program was carried out in Tuwung Village, Pulang Pisau Regency, Central Kalimantan. This program is carried out in order to empower farmers as an effort to increase the productivity of their agricultural products. The aims of this program are; 1). Provide training to farmers related to how to make liquid organic fertilizer from purun plants; and 2).  Determine the effectiveness of the implementation of training on increasing farmers' knowledge in making liquid organic fertilizer. Training activities were presented to the introduction of purun plants and their potential as materials for making liquid organic fertilizer. Next, the activity continued with a demonstration of how to make liquid organic fertilizer from purun plants. Finally, the farmers were asked to practice directly making liquid organic fertilizer. The results of this training had an positive response on the knowledge and skills of farmers in Tuwung Village, Pulang Pisau Regency, in making liquid organic fertilizer. In addition, this activity is considered effective and efficient based on the results of the evaluation in accordance with the target achievement.